2019
DOI: 10.3389/fnhum.2019.00393
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Hybrid Passive BCI for the Modulation of Sustained Attention Using EEG and fNIRS

Abstract: We report results of a study that utilizes a BCI to drive an interactive interface countermeasure that allows users to self-regulate sustained attention while performing an ecologically valid, long-duration business logistics task. An engagement index derived from EEG signals was used to drive the BCI while fNIRS measured hemodynamic activity for the duration of the task. Participants (n = 30) were split into three groups (1) no countermeasures (NOCM), (2) continuous countermeasures (CCM), and (3) event synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 66 publications
(82 reference statements)
1
7
0
Order By: Relevance
“…It meant that different methods explored distinct information and became complementary to each other thereby improving classification performance. The results agreed with the conclusion in the literature [ 29 , 38 , 39 , 42 ]. The present paper is an advance on previous studies because it generated new knowledge about regional information by comparing the foci of independent types of features.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It meant that different methods explored distinct information and became complementary to each other thereby improving classification performance. The results agreed with the conclusion in the literature [ 29 , 38 , 39 , 42 ]. The present paper is an advance on previous studies because it generated new knowledge about regional information by comparing the foci of independent types of features.…”
Section: Discussionsupporting
confidence: 92%
“…Chu et al [ 39 ] stated that the alpha-power of O1 indicated differences between multi-level workloads. Regarding fNIRS, the prefrontal areas were well-accepted for measuring variations in mental workload [ 40 , 41 , 42 ]. However, there was limited research pointing out a determined channel that contributes the most.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the α, β, and θ waves revealed a similar effect in the EEG index when driving in the middle and the rear end of the tunnel. Researchers have recently studied the sustained attention and the attention behavior in distracted driving (Wang et al, 2013 ; Pallavi and Harish, 2016 ; Ding et al, 2019 ; Karran et al, 2019 ), especially the reduction and oscillations of the α - wave energy and the increase in the θ - wave energy (Klimesch et al, 1998 ; Wang et al, 2015 ). It could be speculated that the trends of these wave energies were related to the attention–concentration behavior of drivers during tunnel driving.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2]. The main purpose of a BCI is to equip physically impaired people, especially with motor disabilities, with the facility to communicate with the help of their brain signals [3,4]. A BCI is used to detect and interpret brain signals to control the devices [5].…”
Section: Introductionmentioning
confidence: 99%